KARAKTERISTIK KEILMUAN IAIN SAMARINDA - Khojir, Khojir (LP2M IAIN Samarinda, 2016)
Since the era of STAIN Samarinda to IAIN Samarinda, the characteristics of Islamic studies at IAIN Samarinda has not been crystalized yet. It is an important issue, since the characteristics of Islamic studies in Islamic higher education forms the identity of its image. This study aims to describe the characteristics of Islamic studies at IAIN Samarinda and to formulate the epistemology of Islamic studies at IAIN Samarinda. This is a philosophical qualitative research. The sources of data were from the dean of faculties, the vice-dean of faculties, and the lecturers of IAIN Samarinda. The data were collected by using interviews, documentation, and the study of literature. To validate the data, the researcher used data triangulation. The data, then, analyzed through three stages, namely: data reduction, data display, and data conclusion. The data findings show that the characteristics of Islamic studies at IAIN Samarinda, particulary in the Islamic education study program, tends to implement the multiculturalism-based content. Otherwise, the epistemology of Islamic studies at IAIN Samarinda tends to use ASASI Model (Akademik Sains Islam Malaysia). The implication of this study are: 1) IAIN Samarinda should determine the identity of the characteristics of Islamic studies at IAIN Samarinda, 2) IAIN Samarinda should facilitate the formulation of the epistemology of Islamic studies at IAIN Samarinda, 3) IAIN Samarinda might formulate the concept and the implementaion of science integration both of the aspect of methodology using reflective-conceptual-tentative-problematic and the aspect of its science epistemology using the model of structure of Islamic science.